تحليل معطيات علاقات الارتباط و التأثير بين مكونات رأس المال الفكري و أبعاد أداء العمليات من وجهة نظر المدراء في الشركة العامة لصناعة الالبسة الجاهزة في الموصل - د. أكرم احمد الطويل; د. صباح انور يعقوب (PROSPECTIVE RESEARCHES, 2023)
The research aims at analysis of relationship correlation and the effect between intellectual capital components and operations performance dimensions of the managers opinions in the state company of ready made cloths in Mosul. To a chive this there is a number of main and secondary hypotheses ested by some statistical manners .The data of this research are 85 managers who answered a questionnaire given to them. The research comes up with a number of rsults, the most important ones are the relationship correlation and significant effect between intellectual capital components and operation performance dimensions. According to this, a group of recommendation concerned have been introduced.